Obstructive sleep apnea and its association with sleep quality, daytime sleepiness, depression and attention span - Suzaily Wahab; Rosdinom Razali; Nurhazrina H; Lee, LT; Sara Nadia J; Rafiqah A; Goh, WH; Nuralia AR; Abdullah Sani Mohamed (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Obstructive sleep apnoea (OSA) has multiple physical and psychosocial effects on individuals. Therefore, this study aims to determine the sleep quality, daytime sleepiness, depression and attention span in patients with OSA. This was a cross-sectional study among patients who were recently diagnosed with OSA in a Malaysian hospital. The socio-demographic and clinical data, Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, Patients Health Questionnaire and Comprehensive Trail Making Test were used as instruments. Findings were analysed and presented using Chi-Square, One-Way ANOVA and Independent-Sample T-test statistical analyses. Most of the respondents presented with poor sleep quality and impaired attention span. Approximately, half of the respondents had excessive daytime sleepiness. There were significant associations between sleep quality and daytime sleepiness (p-value=0.051), daytime sleepiness with depression (p-value=0.049) and severity of OSA with depression (p-value=0.026). Daytime sleepiness was significantly associated with working status (p-value=0.009) and driving status (p-value=0.033). In conclusion, most patients with OSA had poor sleep quality, excessive daytime sleepiness, and impaired attention span. Hence, OSA should be diagnosed and treated early, particularly in patients who are still working and actively driving.